(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2021)
Although Coronavirus disease (COVID-19) can affect all age groups, severity of clinical presentation among children and newborns are milder than in adults. Along with classical symptoms, atypical presentation could be noted in the neonate. We report here a case of neonatal COVID-19 where a newborn infant presented with fever, lethargy, respiratory distress and recurrent seizure. Early detection and prompt management is the prerequisite for limiting transmission and reducing neonatal death rate. Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 87-89